The Effect Of Communication, Work Discipline And Compensation On Employee Performance At PT. Indopos Indonesia - Pratama, M Rizky; Handayani, Sri; Prawitasari , Andriyani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this research is to describe and analyze the effect of communication, work discipline and compensation on employee performance at PT. Indoposs Indonesia. This type of research uses quantitative descriptive. The sampling technique used census techniques as many as 24 respondents. The research analysis uses multiple linear regression analysis.Results of analysis There is a positive and significant influence between communication on employee performance at PT. Indoposs Indonesia because tcount is greater than ttable (2.103 > 1.717). then H0 is rejected and Ha is accepted. There is a positive and significant influence between Work Discipline on employee performance at PT. Indoposs Indonesia because the ttable value is 1.717. Then tcount is greater than ttable (2.878 > 1.717). then H0 is rejected and Ha is accepted, there is a positive and significant influence between compensation on employee performance at PT. Indoposs Indonesia because the ttable value is 1.717. So tcount is greater than ttable (2.998 > 1.717), then H0 is rejected and Ha is accepted. There is a positive and significant influence between communication, work discipline and compensation on employee performance at PT. Indoposs Indonesia because Fcount > Ftable (52.968 > 3.47) with a significant value of 0.000. shows that together X1 (Communication), X2 (Discipline) and X3 (Compensation) have a significant influence on employee performance (Y) at PT. Indoposs Indonesia. The results of multiple regression have the equation Y = 11.021 + 0.303 (X1) + 0.380 (X2) + 0.508 (X3) ) + e , because the direction of the regression is positive it can be interpreted that if communication, work discipline and compensation increase, the performance of employees at PT Indoposs Indonesia will also increase